The Effect of Citronella Oil and Sesame Oil Emulsion Coating on The Quality and Storability of Mangoes (Mangifera Indica L.) - Taufik Rahman; Tri Suwandi; Rena Adelia Suryani; Anisa Maharani; Chairani Azahra; Gunawan Gunawan; Lu'lu' Lathifatuzzakiyyah; N Sarah Sri Wahyuni; Nurul Annisa (bionature, 2023)
One of the most promising agricultural commodities is the cultivation of mangoes. One way that can be used to maintain the quality and freshness of the fruit in a simple way is to do an emulsion coating. The purpose of this research was to determine the effect of citronella oil and sesame oil emulsion coating on the quality and storability of mango (Mangifera indica L.). The method used in this study was a Completely Randomized Design (CRD) with two factorial treatments and controls. The first factor was citronella oil under a concentration of 0.5% and 1%. The second factor is sesame oil under a concentration of 0.5% and 1%. The two oils were combined in the emulsion into three treatment combinations, namely S0W2, S2W0, and S1W1. The parameters measured in the observations were hardness, damage, and glucose levels in the fruit. The results showed that the level of hardness of mangoes decreased in the four treatments. Then it was found that there was an effect of delaying the maturity of the fruit with the S1W1 treatment because it was not damaged like the other treatments. While glucose levels in the fruit have increased due to the ripening process. Coating treatment with a ratio of citronella oil concentration of 0.5% to 0.5% sesame oil is the most effective treatment combination in maintaining quality and shelf life because this treatment can delay damage to mangoes.